We have, Discriminant formula for finding roots:
Here,
- x is the root of the equation.
- a is the coefficient of x^2
- b is the coefficient of x
- c is the constant term
1) Given,
3x^2 - 2x - 1
Finding the discriminant,
➝ D = b^2 - 4ac
➝ D = (-2)^2 - 4 × 3 × (-1)
➝ D = 4 - (-12)
➝ D = 4 + 12
➝ D = 16
2) Solving by using Bhaskar formula,
❒ p(x) = x^2 + 5x + 6 = 0
So here,
❒ p(x) = x^2 + 2x + 1 = 0
So here,
❒ p(x) = x^2 - x - 20 = 0
So here,
❒ p(x) = x^2 - 3x - 4 = 0
So here,
<u>━━━━━━━━━━━━━━━━━━━━</u>
Answer:
30
Step-by-step explanation:
14×2=28
28+2=30
i hate riddles
The first one 7/2 represents the change in y over change in x.
For those kinds of questions I would refer to the change in y over change in x method.
Bullet 3 would work because 7/2 doesn’t result to 1. So that’s not the answer.
I hope that helps
Answer:
100
Step-by-step explanation:
sqrt[y] = 10
Apply both side a ^2
then
y = 100
Best regards
Answer:
x = 48
Step-by-step explanation:
First find y
52+y+59 = 180 since they from a straight line
y = 180-59-52
y = 69
Then we know the angles of a triangle add to 180
x+y+63 = 180
x+69+63 = 180
x = 180-69-63
x =48